A minimalistic catalytically-active cell mimetic made of a supra-molecular hydrogel encapsulated into a polymersome. Issue 92 (5th November 2020) - Martí-Centelles, Rosa; Rubio-Magnieto, Jenifer; Escuder, Beatriu
Abstract : A minimalistic multicomponent cell mimetic is constructed from a catalytic low molecular weight fibrillar network and a polymersome compartment. Abstract : A minimalistic multicomponent cell mimetic is described consisting of a fibrillar network formed by the self-assembly of a low molecular weight compound (cytoskeleton-like) that is entrapped into a polymersome (membrane-like), namely a jelly-polymersome. A simple imidazole-appended hydrogelator is used in order to obtain a catalytic nanoreactor able to hydrolyze an ester within the compartment in its self-assembled state.